Comparing the Effectiveness of Health Promotion With Lecture Method and Small Group Discussion (SGD) Method on Breast Self-Examination (BSE) Knowledge in Adolescents - Khairunnisa Nabilatun Rofifah; Nunung Siti Sukaesih; Amanda Puspanditaning Sejati (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2025)
Breast cancer is the leading cause of death among women-related diseases. A delay in diagnosis and treatment contributes to the high fatality rate from breast cancer. Many women remain unaware of BSE (Breast Self-Examination) as an early detection method for breast cancer. Health promotion is essential to increase awareness and knowledge about early detection efforts. Two commonly used health promotion methods are lectures and Small Group Discussions (SGD). This study aimed to evaluate the effectiveness of these methods in improving adolescents' understanding of BSE. A pre-experimental study design (intact group comparison) with a two-group pre-test and post-test approach was conducted. A total of 188 participants were included in the study. Data were collected using a self-developed questionnaire designed to assess adolescents' knowledge of BSE. The Wilcoxon Signed-Rank Test was used to analyze pre-test and post-test results. The findings revealed a significant difference in the effectiveness of health promotion between the lecture method and the SGD method in enhancing BSE knowledge among adolescents, with a p-value of 0.002. Both methods improved BSE knowledge, but the lecture method was more effective.